2022
DOI: 10.1159/000527655
|View full text |Cite
|
Sign up to set email alerts
|

The Choice between Intravenous and Subcutaneous Immunoglobulins: Aspects for Consideration

Abstract: <b><i>Background:</i></b> Intravenous immunoglobulin and subcutaneous immunoglobulin preparations are used to treat primary and secondary immunodeficiencies, as well as autoimmune and inflammatory conditions. <b><i>Summary:</i></b> For certain indications, only defined formulations or routes of administration are approved by health authorities. However, for other diseases, there are more options, and treatment decisions may be based on different aspects, such as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…As a high-dose therapy, IVIG and SCIG preparations are also used for the treatment of autoimmune and inflammatory disorders ( 1 ). Studies over the period of several decades revealed pleiotropic anti-inflammatory mechanisms of action (MoAs) of polyclonal immunoglobulin preparations ( 15 , 29 ).…”
Section: Diversity – the Added Value Of Polyclonal Immunoglobulin Pre...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a high-dose therapy, IVIG and SCIG preparations are also used for the treatment of autoimmune and inflammatory disorders ( 1 ). Studies over the period of several decades revealed pleiotropic anti-inflammatory mechanisms of action (MoAs) of polyclonal immunoglobulin preparations ( 15 , 29 ).…”
Section: Diversity – the Added Value Of Polyclonal Immunoglobulin Pre...mentioning
confidence: 99%
“…Polyclonal immunoglobulin (Ig) preparations, administered via intravenous (IVIG) or subcutaneous (SCIG) routes, are successfully used as replacement therapy in immunodeficiencies and for the treatment of select autoimmune or inflammatory disorders ( 1 ). These preparations consist of pooled human IgG derived from the plasma of thousands of donors and in contrast to therapeutic monoclonal antibodies encompass an immense range of reactivities ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%